Peran Guru Sosiologi Dalam Menanamkan Sikap Toleransi Paham Keagamaan Di Lingkungan Pesantren: Studi Kasus Siswa SMAI Sunan Gunung Jati Tulungagung - Zulfa Rofi’atunnisa; Binti Maunah (Politeknik Kampar, 2024)
This research is based on researcher's concern that Islamic boarding school graduates, especially those with a Salaf background, have an exclusive mindset when they return to society they are less able to implement their mission as religious agents in the social environment due to being surprised by the diversity of society and sects in Islam. This is because the graduates of Islamic boarding school believe that anything that is not the same as what they understood is a mistake. Therefore, formal school teachers have a role and duty as a lens to provide insight for students in the current era where Islamic boarding schools have intensively built formal institutions in their environment. To explore this problem, the researcher formulated the research focus as follows: 1.) What is the role of the Sociology teacher in instilling an attitude of religious tolerance in the Islamic boarding school environment for X grade students at SMAI Sunan Gunung Jati Tulungagung? 2.) What are the Sociology teachers' efforts to instill an attitude of religious tolerance in X grade students at SMAI Sunan Gunung Jati Tulungagung? 3.) What is the impact of the role of sociology teachers in instilling tolerance of religious understanding in the pesantren environment on class X students at SMAI Sunan Gunung Jati Tulungagung., to determine the efforts of Sociology teachers in instilling an attitude of religious tolerance in the Islamic Boarding School environment in X grade students at SMAI Sunan Gunung Jati Tulungagung, to know the impact of the role of sociology teachers in instilling religious tolerance in X grade students at SMAI Sunan Gunung Jati Tulungagung. This research used descriptive qualitative research by using a case study approach. The methods used in this research were participant observation, in-depth interviews, and documentation. Meanwhile, the data analysis techniques used were data reduction, data presentation and inference. In checking data validity, the researcher used extended participation, persistence or regularity of observation and triangulation. The result of the study showed that 1.) The role of sociology teachers in educating students about religious tolerance is to teach, guide, train, assess, evaluate and provide direction to students by providing feedback to exchange ideas and insights in the discussion process, then give understanding in sociology materials and train students to respect differences 2.) Teachers’ effort in instilling an attitude of religious tolerance in students by strengthening character education. Then, by using learning media such as showing or displaying videos related to actions of religious tolerance, providing hot issues that exist in community life about lack of tolerance in religion. Besides, students are given concrete examples of teachers' attitudes 3.) Impact of the role of sociology teachers in educating an attitude of religious tolerance is that the students have a better insight of the importance of tolerance. In its implementation, there are changes in students' attitudes towards knowledge and understanding so that students' character is formed.